Editorial - Smyrnova-Trybulska, Eugenia (International Journal of Research in E-learning, 2020)
The policy goal of the technology literacy approach is to enable learners, citizens, and the workforce to use ICT in order to support social development and to improve economic productivity. Related policy goals include increasing enrolments, making high-quality resources available to everyone, and improving literacy skills. Teachers should be aware of these goals and be able to identify the components of education reform programmes that correspond to these policy goals. Corresponding changes in the curriculum entailed by this approach might include improving basic literacy skills through technology and adding the development of ICT skills into relevant curriculum contexts (UNESCO, 2011). The present volume includes eight articles gathered in four chapters. Chapter I, entitled “ICT-tools and E-learning Methodology in Contemporary University", Chapter II – “Distance Learning Technologies in Different Countries” – con- tains two articles. Chapter III – “ICT and Multicultural Competencies Developing Supported E-learning”, Chapter IV – “Reports”. It can be stressed that strategies of access to ICT resources are the essential elements of lifelong learning (UNESCO Incheon Declaration, 2016). Except for Web 2.0 and Web 3.0 technologies, MOOCs (Massive Open Online Courses) have continued to attract considerable media coverage, as governments and universities respond to the open and online education movement. International teams and networks – such as the international consortium of the IRNet project – can make a fundamental contribution to the further development of strategies and methodologies of modern education.